2022
DOI: 10.21203/rs.3.rs-1805527/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Investigating Students’ Perceptions Towards Artificial Intelligence in Medical Education

Abstract: Objective: Implementing a reform in medical education requires students’ awareness regarding the importance of artificial intelligence (AI) in modern medicine practice. This study aimed to investigate students’ perceptions towards AI in medical education.Subject and Methods: A cross-sectional survey was conducted from June 2021 until November 2021, using an online questionnaire to collect data from medical students in the faculty of medicine at Kuwait University.Results: The response rate was 51.0%, with a sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…They neither agree nor disagree with the notion. This aligns with the findings from Buabbas et al [29] and Moldt et al [31], where 78•7% and 83% of participants, respectively, expressed skepticism about AI eventually replacing the roles of physicians in the future.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…They neither agree nor disagree with the notion. This aligns with the findings from Buabbas et al [29] and Moldt et al [31], where 78•7% and 83% of participants, respectively, expressed skepticism about AI eventually replacing the roles of physicians in the future.…”
Section: Discussionsupporting
confidence: 87%
“…The majority of participants felt they knew little to nothing about ChatGPT [28]. According to Buabbas' study, 84% of Kuwaiti medical students did not have any training on the use of AI [29]. It is worth noting that more than 80% of our participants indicated an interest in learning more about ChatGPT's healthcare applications, with time restrictions being the primary barrier for 40% of them.…”
Section: Discussionmentioning
confidence: 96%
“…These concerns may be rooted in the uncertainty surrounding AI's role in healthcare and the need for clear guidance and education on the integration of AI into medical practice. Other research, conducted in Kuwait, found overall positive attitudes towards AI in medical education and a consensus that AI-based medical practice is required [19]. These differences in attitudes across regions could be influenced by variations in the readiness and exposure of these countries to AI in healthcare, as well as the cultural and educational contexts specific to each region.…”
Section: Discussionmentioning
confidence: 93%
“…A similar study on the perception of artificial intelligence (AI) among medical students showed that most students were positive and willing to adopt it in medical education. 11 Most of the previously conducted studies addressed AI-related knowledge in medical students and dentistry students have never been specifically tested for knowledge and attitude towards Chat-GPT. In a Canadian study, (78.9%) of medical students showed a good understanding of AI, however, in the same study students could not answer the true/false questions containing facts and fallacies about AI.…”
Section: Discussionmentioning
confidence: 99%